2010
DOI: 10.1007/s12564-010-9136-7
|View full text |Cite
|
Sign up to set email alerts
|

Individualism, collectivism, and client expression of different emotions: their relations to perceived counselor effectiveness

Abstract: This study examined how individualism, collectivism, and counselor emphasis of different client emotions were related to perceived counselor effectiveness. Data were collected from 192 (122 women and 70 men) Korean students attending a large university in South Korea and from 170 (115 women and 55 men) American students attending a large Midwestern university in the United States. Participants read a counseling script in which a counselor emphasized client expression of either egofocused emotions (e.g., anger)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…According to a large-scale comparison of display rules across 32 countries by Matsumoto et al (2008a), this might actually extend to general in-and out-group effects: Although participants from collectivistic societies reported less expressivity in general, they actually endorsed negative emotional displays toward strangers much more than participants with an individualistic background. This observation in turn connects to a growing body of literature about the "appropriateness" of selected emotional states (e.g., Kitayama et al, 2000;Eid and Diener, 2001;Seo, 2011), which has suggested that individualistic cultures strongly favor displays of personal success (e.g., pride, joy), whereas collectivists prefer emotions that highlight interrelatedness-even if their expression emphasizes personal failure (e.g., guilt, shame). Considering the core principles of both cultural orientations, this actually makes perfect sense: Just as the visible acknowledgment of personal shortcomings highlights the investment in the collective well-being, turning guilt and embarrassment into other-focused emotions (Markus and Kitayama, 1991), displays of pride or happiness mostly serve to express private gain, therefore meshing with a more individualistic philosophy (i.e., ego-focused emotions).…”
Section: Display Rules and Types Of Emotionsupporting
confidence: 67%
“…According to a large-scale comparison of display rules across 32 countries by Matsumoto et al (2008a), this might actually extend to general in-and out-group effects: Although participants from collectivistic societies reported less expressivity in general, they actually endorsed negative emotional displays toward strangers much more than participants with an individualistic background. This observation in turn connects to a growing body of literature about the "appropriateness" of selected emotional states (e.g., Kitayama et al, 2000;Eid and Diener, 2001;Seo, 2011), which has suggested that individualistic cultures strongly favor displays of personal success (e.g., pride, joy), whereas collectivists prefer emotions that highlight interrelatedness-even if their expression emphasizes personal failure (e.g., guilt, shame). Considering the core principles of both cultural orientations, this actually makes perfect sense: Just as the visible acknowledgment of personal shortcomings highlights the investment in the collective well-being, turning guilt and embarrassment into other-focused emotions (Markus and Kitayama, 1991), displays of pride or happiness mostly serve to express private gain, therefore meshing with a more individualistic philosophy (i.e., ego-focused emotions).…”
Section: Display Rules and Types Of Emotionsupporting
confidence: 67%
“…Moreover, people from collectivistic cultures are encouraged to display other‐focused emotions (e.g., sympathy/empathy, feelings of interpersonal communion) for which others are the primary referent. Conversely, individuals from individualistic cultures are encouraged to express ego‐focused emotions such as anger, frustration (Seo, ). Therefore, parentified Korean children are likely to internalize their feelings and difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Farber (2006) highlighted the role that culture plays in self-disclosure, which may impact how a rupture is expressed. Individuals with values that lean toward collectivism may not only hold authority figures in high esteem but also refrain from disclosing information that would present another person in an unfavorable light (Seo, 2011). Asian immigrant clients, for example, may be less inclined to disclose how they feel about their therapists out of respect for their position or to maintain harmony in the relationship.…”
Section: Detection Of Ruptures In Sessionmentioning
confidence: 99%